How Well Public Service Motivation and Job Satisfaction in Enhancing the Effect of Compensation on Job Performance? - Ida Bagus Agung Dharmanegara; Riza Bahtiar Sulistyan; Iin Agustina (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2021)
This study aims to examine the relationship between compensation and public service motivation, job satisfaction and job performance from Public High Schools in Badung Regency, Denpasar Bali. The theoretical basis used is the concept of fairness in compensation, motivational bases in public service and value-percept theory in job satisfaction toward individual performance. The study was conducted on employees of a public high school in Badung Regency, Denpasar Bali, involving all employees who were respondents in this study. The research model built in this study was tested using a quantitative paradigm and specifically path analysis was used to answer research questions about how the pattern of interrelationships between the four variables observed in this study. The results of the study indicate that compensation is very important in increasing public service motivation and employee job satisfaction, although on the other hand compensation cannot have a direct impact on employee performance. Considering that there is an important effect of public service motivation and job satisfaction on job performance, it is believed that the effect of compensation can improve job performance through public service motivation and job satisfaction.